2012
DOI: 10.1002/art.37711
|View full text |Cite
|
Sign up to set email alerts
|

Head‐to‐head comparison of subcutaneous abatacept versus adalimumab for rheumatoid arthritis: Findings of a phase IIIb, multinational, prospective, randomized study

Abstract: ObjectiveThere is a need for comparative studies to provide evidence-based treatment guidance for biologic agents in rheumatoid arthritis (RA). Therefore, this study was undertaken as the first head-to-head comparison of subcutaneous (SC) abatacept and SC adalimumab, both administered along with background methotrexate (MTX), for the treatment of RA.MethodsPatients with active RA who were naive to treatment with biologic agents and had an inadequate response to MTX were randomly assigned to receive 125 mg SC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
186
0
10

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(207 citation statements)
references
References 62 publications
9
186
0
10
Order By: Relevance
“…Comparable improvements from baseline to year 1 were seen in fatigue with SC abatacept and adalimumab (−23.2% SC abatacept versus −21.4% adalimumab; adjusted treatment difference −1.8% [95% CI −5.8, 2.2]) 12. Results for pain over 1 and 2 years have also been presented previously 14.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Comparable improvements from baseline to year 1 were seen in fatigue with SC abatacept and adalimumab (−23.2% SC abatacept versus −21.4% adalimumab; adjusted treatment difference −1.8% [95% CI −5.8, 2.2]) 12. Results for pain over 1 and 2 years have also been presented previously 14.…”
Section: Introductionmentioning
confidence: 63%
“…Abatacept is a T‐cell costimulation modulator that has shown efficacy in patients with RA in a wide range of disease and treatment durations 4, 5, 6, 7, 8, 9, 10, 11. The AMPLE (Abatacept versus Adalimumab Comparison in Biologic‐Naive RA Subjects with Background MTX) trial, the first head‐to‐head trial comparing biologic DMARDs in patients with RA receiving MTX, demonstrated noninferiority for abatacept versus adalimumab by the ACR 20% improvement response (ACR20) at year 1 (64.8% subcutaneous [SC] abatacept versus 63.4% adalimumab; estimated difference between treatments 1.8% [95% confidence interval (95% CI) −5.6, 9.2] in an intent‐to‐treat analysis) 12. In AMPLE, there was a similar time of onset of ACR20 response in both treatment groups, with the response maintained up to year 2 13.…”
Section: Introductionmentioning
confidence: 99%
“…We also note that 31% of patients had missing MBDA data at year 2 compared with year 1, which exceeds the 8.5% decline in total patient numbers from the end of year 1 to the end of year 2 in the overall AMPLE trial (2,22).…”
Section: To the Editormentioning
confidence: 73%
“…We read with great interest the report by Fleischmann et al (1), which presents post hoc analyses of multi-biomarker disease activity (MBDA) scores measured using serum samples from AMPLE (Abatacept versus Adalimumab Comparison in Biologic-Naive Rheumatoid Arthritis Subjects with Background Methotrexate), a study sponsored by Bristol-Myers Squibb that compared abatacept versus adalimumab in rheumatoid arthritis (RA) patients with inadequate response to methotrexate (2). The article reported 3 main results: 1) in the first year, mean MBDA scores decreased significantly less with abatacept treatment than with adalimumab, yet clinical responses by Disease Activity Score in 28 joints using the C-reactive protein level (DAS28-CRP) (3) were similar between the 2 treatment groups; 2) RA disease activity category (i.e., low, moderate, or high) as classified by the MBDA score was often discordant with the classification according to the DAS28-CRP, Clinical Disease Activity Index (CDAI) (4), Simplified Disease Activity Index (SDAI) (5), or Routine Assessment of Patient Index Data 3 (6); and 3) radiographic data were interpreted as demonstrating that MBDA scores were not associated with radiographic progression.…”
Section: To the Editormentioning
confidence: 99%
“…Consequently, the present analysis is the first to integrate all available evidence directly comparing a combination of DMARDs versus a biologic treatment plus methotrexate, and is also the first to estimate the effect at consecutive time points during a period of 2 years. Although only TNF inhibitors were investigated, it is likely that the present results could be extended to other biologic agents, as the biologic agents in general have been shown to be equally efficacious (2,22,24).…”
Section: Discussionmentioning
confidence: 97%